PERTUMBUHAN SEMAI JATI (Tectona grandis L.f) PADA PERBANDINGAN MEDIA TANAH DAN PUPUK ORGANIK LIMBAH KULIT KAKAO - Muhajir, Muhajir; Muslimin, Muslimin; Umar, Husain (Universitas Tadulako, 2015)
Teak (Tectona grandis L.f) is a wood commodity that has a very high economic value. Teak in condition of strength grade I dan durability grade I-II as well as a high artistic value, has a market price of domestic and abroad. The use of fertilizer is needed to supply nutrients for plant growth. The use of cacao (Theobroma cacao L) rind waste organic fertilizer and other materials that are organic in nature are intended to reduce problems arising from the use of chemicals that can damage the soil and the environment. Procurement of quality seeds needed the support of the quality medium and able to provide sufficient nutrients for the growth of seedlings as well as meet the requirements of seedling growth. By the availability of nutrients for seedlings, seedling growth will be more optimal, the use of the medium can be an organic fertilizer that is more environmentally friendly. The use of fertilizer is needed to supply nutrients for the growth of seedlings. The use of organic fertilizers that made of cacao rind waste and other materials that are organic. It is still rare rind waste compost medium use cacao as teak seedling medium. The objective of this research was to find out the teak (Tectona grandis L.f) seedling growth in comparison soil medium and cacao (Theobroma cacao. L) rind waste organic fertilizer. Keywords : seedling, Tectona grandis L.f, cacao compost